50 years of channel change on a reach of the Big Blue River, northeast Kansas - Graf, Nicholas E. (Kansas State University, 2008)
River migration has resulted in a land owner losing 80% of his farmable land along the west bank of a reach h of the Big Blue River near Marysville, Kansas. Analysis of meander geometry and meander movement revealed that a single meander is moving down valley, resulting in the loss of farmland. The rate and direction of river meander migration were measured using photogrammetric analysis of aerial photographs and topographic maps covering a period from 1956 to 2006. The greatest annual rates of channel migration and farmland erosion were closely associated with high flow events on the river between 1983 and 1986 and between 1986 and 1988. Analysis of recurrence interval, riparian vegetation, and bend curvature indicate that the rates of farmland lost and total meander migration are explained largely by the magnitude of floods. The direction in which the meander moved is largely explained by the bend curvature.
Keywords: River Meanders; Big Blue River, Kansas; Erosion; Fluvial Geomorphology; Photogrammetry; Geography (0366); Geology (0372)